Validacion de un modelo de elementos finitos para representar el ensayo de la barra dividida de Hopkinson (SHPB) (2017)
Validation of a finite element model that could represent the Split Hopkinson pressure bar (SHPB), trying to corroborate results obtained in an experimental test (wave strain). Developing a methodoly that could be applied to validate differents finite elements models for differents Split hopkinson pressure bar configurations.--Tomado del Formato de Documento de Grado.